2021
DOI: 10.1016/j.waojou.2021.100536
|View full text |Cite
|
Sign up to set email alerts
|

Impact of specific immunotherapy and sting challenge on the quality of life in patients with hymenoptera venom allergy

Abstract: Background An experienced life-threating anaphylactic reaction to hymenoptera venom can sustainably impair patients’ quality of life (QoL). Besides carrying emergency medication, venom-specific immunotherapy (VIT) exists as a causal treatment of allergy. Objective This study aimed to examine QoL, anxiety, depression, and physical and mental health in patients allergic to hymenoptera venom before and during VIT and the impact of a tolerated sting challenge (SC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
0
12
0
2
Order By: Relevance
“…Irrespective of the general anxiety level, the time elapsed since the allergic reaction, reaction severity or age, women showed a stronger impairment in their HRQL than men 7 . Many studies confirmed this correlation of female sex and a stronger impairment on HRQL 62,71,72 . In a German study using sociodemographic and disease‐specific characteristics as well as the HADS, also female patients with mild SRs showed higher disease‐related anxiety levels than men 73 .…”
Section: Hymenoptera Venommentioning
confidence: 95%
See 1 more Smart Citation
“…Irrespective of the general anxiety level, the time elapsed since the allergic reaction, reaction severity or age, women showed a stronger impairment in their HRQL than men 7 . Many studies confirmed this correlation of female sex and a stronger impairment on HRQL 62,71,72 . In a German study using sociodemographic and disease‐specific characteristics as well as the HADS, also female patients with mild SRs showed higher disease‐related anxiety levels than men 73 .…”
Section: Hymenoptera Venommentioning
confidence: 95%
“…Sting challenges in patients receiving VIT are also associated with a significant improvement in HRQL, meaning that some patients trust their therapy only after the demonstration of its efficacy through a sting challenge 62,72,78 …”
Section: Hymenoptera Venommentioning
confidence: 99%
“…Such an outcome has been confirmed in a recent study, proving that the improved HRQL associated with VIT can be further increased by a tolerated sting challenge, that it is conceivable it can reassure the patients. A more marked effect was seen in the female gender (27). A fairly recent review has highlighted all aspects of Hymenoptera venom allergy and VIT, also considering adherence and quality of life, which were usually superior to those of other models of immunotherapy (28), although it remains to be clarified how much the results may vary according to the different centers that practice VIT (11).…”
Section: Quality Of Lifementioning
confidence: 99%
“…В рутинной клинической практике предпочтительнее классификация, предложенная экспертами Европейской академии аллергии и клинической иммунологии (EAACI) [12] Для диагностики инсектной аллергии почти всегда достаточно изучения анамнеза. Обнаружение аллерген-специфических IgE-антител к аллергенам яда in vitro, которые обнаруживаются в 90% случаев, причем отмечается высокая корреляция между результатами кожных проб и лабораторного тестирования и/или положительные кожные тесты -скарификационный и prick-тест (предпочтительнее) с аллергеном яда насекомых, -позволяет верифицировать диагноз аллергии к яду насекомых [7,12,23]. При местных аллергических реакциях положительные кожные пробы регистрируются в 70-80% случаев, при системных в 90% случаев [18].…”
Section: неотложные состоянияunclassified
“…Единственным лечением, которое может потенциально предотвратить развитие системных реакций от ужаления насекомых, является АСИТ, т. е. повторное введение аллергена в повышающихся дозах через регулярные промежутки времени для модуляции иммунного ответа [7,9].…”
Section: неотложные состоянияunclassified